Peningkatan Keterampilan Menulis Kalimat Dengan Menerapkan Model Concept Sentence Siswa Kelas XI IPA 7 SMAN 1 Waru - IMADHINI INDRAYANA, PUTRI (LATERNE, 2013)
In the teaching of German language there are four competence namely listening, speaking, reading and writing. Writing competence is a productive and complex activity. There are so many component such us, grammatik rule, vocabulary, coherence, diction ,etc,they must be mastered. Strategy of concept sentence is one of learning model that can increase writing skill. Keywords: writing competence, Models Concept Sentence